MONEY POLITICS AS CULTURE: KEPYUR AND RATIONAL CHOICE AMONG RURAL VOTERS IN KENDAL REGENCY ELECTIONS - Prasetyo, Kuncoro Bayu; Khasanah, Zulfa Yuladia Nur; Aila, Najwa Mutiara (Sosiohumaniora, 2026)
Kepyur is a local term used by the people of Kendal Regency to refer to the practice of money politics in elections. Kepyur practices have become a cultural norm in Kendal, occurring in village head elections, parliamentary elections, and regional head elections. This study aims to explain the factors behind the prevalence of kepyur practices and analyze their relationship with voters’ rational choices. The research employed a qualitative descriptive method using a case study approach, focusing on the 2020 regional election in Kalibareng Village. Data were collected through observation, interviews, and documentation. Data analysis involved data reduction, data display, and conclusion drawing based on rational choice theory. The results indicate that money politics in the form of kepyur is not considered reprehensible by the community. For campaign teams, distributing kepyur to voters is viewed as a rational strategy to secure electoral victory for their candidates. Similarly, for community members, kepyur is perceived as a rational consequence, as voting for a candidate entails losing time that could otherwise be spent working. Unlike conventional money politics, which is generally associated with coercive vote buying, political bribery, or explicit electoral exchange, kepyur is socially legitimized and embedded in everyday economic practices. It is not understood as an illegal transaction but rather as informal compensation for lost livelihoods on election day. Kepyur has shifted political rational choice toward economic rationality, as voting rights can be exchanged for financial benefits that substitute for lost income on election day.